Recent advances in luminescent metallacycles/metallacages for biomedical imaging and cancer therapy. Issue 43 (12th October 2022) - Pang, Yida; Li, Chonglu; Deng, Hongping; Sun, Yao
Abstract : Rational design of luminescent metallacycles/metallacages for advanced biomedical imaging and cancer therapy. Abstract : Small molecule metal-based drugs have shown great achievements in preclinical and clinical applications. In particular, platinum based antitumor drugs are well established in current cancer chemotherapy. However, they face problems such as poor selectivity, severe toxicity and side effects, strong drug resistance, poor uptake/retention in vivo, and difficulty in monitoring the therapeutic effect in real time, which largely limit their widespread use in clinical applications. The metallacycles/metallacages formed by the coordination-driven self-assembly of highly emitting ligands can solve the above problems. Importantly, acceptors with chemotherapeutic properties in the metallacycles/metallacages can be combined with luminescent ligands to achieve a combination of chemotherapy, imaging contrast agents and multifunctional therapeutic platforms. Here, this review provides an insight into the paradigm of self-assembled metallacycles/metallacages in biological applications, from mono-chemotherapeutic drugs to excellent fluorescent imaging contrast agents and multifunctional therapeutic platforms.